The Web of Life: A New Synthesis of Mind and Matter - Fritjof Capra (Flamingo, 1997)
During the past twenty-five years, scientists have challenged conventional views of evolution and the organization of living systems and have developed new theories with revolutionary philosophical and social implications. Fritjof Capra has been at the forefront of this revolution. In The Web of Life, Capra offers a brilliant synthesis of such recent scientific breakthroughs as the theory of complexity, Gaia theory, chaos theory, and other explanations of the properties of organisms, social systems, and ecosystems. Capra's surprising findings stand in stark contrast to accepted paradigms of mechanism and Darwinism and provide an extraordinary new foundation for ecological policies that will allow us to build and sustain communities without diminishing the opportunities for future generations.[from the publisher].